Pea protein hydrolysate reduces blood glucose in high-fat diet and streptozotocin-induced diabetic mice - Liao, Wang; Cao, Xinyi; Xia, Hui; Wang, Shaokang; Chen, Liang; Sun, Guiju (Frontiers in Nutrition, 2023)
Food proteins have been recognized as an ideal source to release bioactive peptides with the potential to intervene nutrition related chronic diseases, such as cardiovascular diseases, obesity and diabetes. Our previous studies showed that pea protein hydrolysate (PPH) could suppress hepatic glucose production in hepatic cells via inhibiting the gluconeogenic signaling. Thus, we hypothesized that PPH could play the hypoglycemic role in vivo. In the present study, the mice model with type 2 diabetic mellitus (T2DM) was developed by high-fat diet and low dose of streptozotocin injections. PPH was administered orally with a dosage of 1000 mg/kg body weight for 9 weeks, followed by the downstream biomedical analyses. Our results showed that the 9-week treatment of PPH could reduce fasting blood glucose by 29.6% and improve glucose tolerance in the T2DM mice. The associated mechanisms included suppression of the gluconeogenic pathway, activation of the insulin signaling and modulation of the renin angiotensin system in the liver of the diabetic mice. In addition, the levels of pro-inflammatory markers in both liver and serum were reduced by the PPH treatment. Findings from this study could provide rationale to incorporate PPH into functional foods or nutraceuticals for glycemic control.